Catalytic Asymmetric Synthesis of Cyclohexanes by Hydrogen Borrowing Annulations. (7th August 2019) - Armstrong, Roly J.; Akhtar, Wasim M.; Young, Tom A.; Duarte, Fernanda; Donohoe, Timothy J.
Abstract: Hydrogen borrowing catalysis serves as a powerful alternative to enolate alkylation, enabling the direct coupling of ketones with unactivated alcohols. However, to date, methods that enable control over the absolute stereochemical outcome of such a process have remained elusive. Here we report a catalytic asymmetric method for the synthesis of enantioenriched cyclohexanes from 1, 5‐diols via hydrogen borrowing catalysis. This reaction is mediated by the addition of a chiral iridium(I) complex, which is able to impart high levels of enantioselectivity upon the process. A series of enantioenriched cyclohexanes have been prepared and the mode of enantioinduction has been probed by a combination of experimental and DFT studies. Abstract : Ein katalytisches asymmetrisches Verfahren für die Synthese von enantioangereicherten Cyclohexanen aus racemischen 1, 5‐Diolen mittels Hydrogen‐Borrowing‐Katalyse wird beschrieben. Diese Reaktion wurde durch einen chiralen Iridium(I)‐Komplex vermittelt, der dem Prozess eine hohe Enantioselektivität verleihen kann.